Thrombocytopenia in early pregnancy predicting partial haemolysis, elevated liver enzyme and low platelet count syndrome: a case report and review of literature - Nagandla, Kavitha; Kumar, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The incidence of thrombocytopenia in pregnancy is 6-10% and is classically defined as a platelet count of less than 150,000/ L. Counts less than 100,000 to 150,000/L are considered mild, 50,000 to 100,000/L as moderate, and less than 50,000/L are considered as severe thrombocytopenia. It is the second most common hematological condition in pregnancy with anaemia being the leading cause. Thrombocytopenia may be related to disorders that are intrinsic to pregnancy such as gestational thrombocytopenia that is seen in three-fourths of all cases. The second common cause is hypertensive disorders in pregnancy more commonly seen in severe pre-eclampsia in 21% and in HELLP (haemolysis, elevated liver enzyme and low platelet count) that accounts for 12% of thrombocytopenia cases in pregnancy. This case report revisits the diagnosis of partial HELLP under the background of preeclampsia that warrants aggressive treatment like complete HELLP syndrome to optimize the maternal and fetal outcome.